The Stoic Paradigm of Ethics as a Philosophical Tool for Objectifying the Concepts of Organizational Ethics, Corporate Social Responsibility, and Corporate Governance - Kourtoglou, Olga; Vavouras, Elias; Sariannidis , Nikolaos (Conatus - Journal of Philosophy, 2024)
In this article, the relationship between ethics in general and business ethics in particular to Stoic philosophy is investigated. Stoic ethics is used as a research tool, which step-by-step deciphers the position of the human as a functional part of a larger organization, such as the natural environment or civil society. Ethics is inextricably linked to the rational, free choice of what is right for both the individual and the total organism. Ethical rightness imposes a form of rational order within the organization, in the sense that each part must perform the function appropriate to its abilities. At the maximum degree of ethical integration stands the paradigm of the Stoic sage as a model of a virtuous leader, who is able to understand the causes of each decision or action and direct the organization towards the set goal. From this perspective, concepts such as leadership, organizational ethics, or corporate social responsibility acquire an objective status and view the philosophical cosmopolitanism of the Stoic sage as a timeless example of ethical rightness.